Knowledge & Awareness about COVID-19 and the Practice of Respiratory Hygiene and Other Preventive Measures among Patients with Diabetes Mellitus in Pakistan - Kumar Ajay; Ishfaq Hamza; Khemani Deepika; Ghori, Qurat-ul-Ann Ramsha; Sohail Hamza; Hassan Syeda Maria; Ghazanfar Shamas; Khan Muhammad Adil Aftab; Ahmed Moiz; Abbas Kiran (European Scientific Journal, ESJ, 2020)
COVID-19 is a global pandemic that has emerged and it is rapidly spreading throughout the world and subsequently causing great damage to the global economy and health-care. Patients with diabetes or other comorbidities are at a greater risk of developing severe illness. Knowledge and awareness are key elements to stimulate practice of preventive measures. The present study evaluated the level of knowledge and awareness about COVID-19 among individuals with diabetes and their compliance with the preventive measures against it. A total of 242 individuals who were diagnosed with diabetes mellitus and were 18 years or older participated in the study. The data was collected using an interview based questionnaire. Data was analyzed using Statistical Package for Social Sciences(SPSS) version 24. The mean age ± SD of the study population was 50.78 ± 11.24 years. In this study, 215 (88.8%) participants were aware that COVID-19 is caused by a virus and the disease is spread through droplets after sneezing or touching and shaking hands with an infected person (78.5%). However, only half the study populace regularly monitored their glucose level and complied with the “sick day rules” that is applicable during this pandemic. The present study indicates that despite the adequate knowledge and awareness about the coronavirus disease, the study participants were non-compliant with the practice of preventive and precautionary measures against the pandemic.